A Phenolic-rich Extract of Cocoa (Theobroma cacao L.) Beans Impairs the Pathogenic Properties of Porphyromonas gingivalis and Attenuates the Activation of Nuclear Factor Kappa B in a Monocyte Model - Vaillancourt, Katy; Ben Lagha, Amel; Grenier, Daniel (Frontiers in Oral Health, 2022)
Periodontitis, an inflammatory disease that affects tooth-supporting tissues, is the result of a polymicrobial infection involving mainly Gram negative anaerobic bacteria. The aim of the present study was to investigate the effects of a phenolic-rich extract of cocoa (Theobroma cacao L.) beans on the pathogenic properties of Porphyromonas gingivalis, which is well-known as a keystone pathogen in the development of periodontitis. The effect of the cocoa extract on P. gingivalis-induced activation of the nuclear factor kappa B (NF-B) transcription factor in a monocyte model was also assessed. The cocoa extract, whose major phenolic compound was epicatechin, inhibited the growth, hemolytic activity, proteolytic activities, and adherence properties (basement membrane matrix, erythrocytes) of P. gingivalis in a dose-dependent manner. It also protected the barrier function of a keratinocyte model against the deleterious effects mediated by P. gingivalis, and attenuated reactive oxygen species (ROS) production by oral keratinocytes treated with P. gingivalis. Lastly, the cocoa extract showed an anti-inflammatory property by preventing P. gingivalis-induced NF-B activation in monocytes. In conclusion, this in vitro study highlighted the potential value of an epicatechin-rich extract of cocoa beans for preventing and/or treating periodontal diseases.